Teacher technology usage, a catalyst for principal digital leadership practice - Zhu, Rui; Alias, Bity Salwana; Hamzah, Mohd Izham Mohd; Wahab, Jamalullail Abdul (International Journal of Evaluation and Research in Education (IJERE), 2025)
In the digital age, university principals and teachers share the same responsibility for improving educational digital transformation. However, their performance remains disadvantaged. This study aims to investigate the relationship between principal digital leadership and teacher technology usage, and explores how teacher technology usage contributes to principal digital leadership. The study employed a quantitative method, collecting data from 500 teachers across 25 universities in Jilin Province, China. Pearson correlation analysis examined the association between principal digital leadership and teacher technology usage, while multiple regression explored how teacher technology usage contributes to principal digital leadership practices. The results revealed a positive relationship between principal digital leadership and teacher technology usage. All four dimensions of teacher technology usage contribute to digital leadership practices, with the professional development dimension showing the greatest impact. Overall, these findings prove that teacher technology usage indeed catalyzes principal digital leadership practices, which contributes to understanding of the interaction in leadership and provides a new perspective for enhancing principal digital leadership. It implies that principals and teachers can grow together in their interactions. Therefore, strengthening teachers’ professional development can contribute to principal digital leadership practice.